Feasibility of differential quantification of 3D temporomandibular kinematics during various oral activities using a cone-beam computed tomography-based 3D fluoroscopic method - Chien-Chih Chen; Cheng-Chung Lin; Tung-Wu Lu; Hao Chiang; Yunn-Jy Chen (Elsevier, 2013)
Background/purpose: The measurement of mandibular kinematics is critical for studying the function of the temporomandibular joint (TMJ) and for relevant clinical applications. However, none of the existing methods allows the measurement of three-dimensional (3D) in vivo motion of the joint during dynamic functional movements without artifactual interference. The purpose of this study was to demonstrate the feasibility of a newly developed cone-beam computed tomography (CBCT)-based 3D fluoroscopic method in differentiating rigid-body kinematics of the TMJ during various functional activities. Materials and methods: One healthy individual was asked to undergo a CBCT scan and fluoroscopic imaging of her mandible and maxilla during various functional activities. CBCT-based 3D fluoroscopy was used to measure the 3D kinematics of the TMJ. Results: The 3D rigid-body kinematics of the mandible, movement trajectories of the centers of the TMJ and the midpoint of the interincisal edge were measured during functional activities. Conclusion: A new CBCT-based 3D fluoroscopic method was proposed and shown to be capable of quantitatively differentiating TMJ movement patterns among complicated functional activities. It also enabled a complete description of the rigid-body mandibular motion and descriptions of as many reference points as needed for future clinical applications. It will be helpful for dental practice and for a better understanding of the functions of the TMJ.